Fully Automatic Left Ventricle Segmentation Using Bilateral Lightweight Deep Neural Network - Muhammad Ali Shoaib; Joon Huang Chuah; Raza Ali; Samiappan Dhanalakshmi; Yan Chai Hum; Azira Khalil; Khin Wee Lai (Multidisciplinary Digital Publishing Institute, 2024)
Indexed by WOS/Scopus